FIRST-PRINCIPLES STUDY OF Sn-DOPING EFFECTS ON THE ELECTRONIC AND OPTICAL PROPERTIES OF ZnO - Rini Anggraini Pakpahan; Suryanti Suraja Pulungan (Indonesian Physical Review, 2026)
In this work, the effects of substitutional Sn doping on the electronic and optical properties of ZnO were investigated using first-principles Density Functional Theory (DFT) calculations within the Generalized Gradient Approximation of Perdew–Burke–Ernzerhof (GGA-PBE). A 2 × 2 × 2 wurtzite ZnO supercell was employed, where Sn atoms substituted Zn atoms at concentrations of 6.25, 12.50, and 18.75% on Zn sites. Structural optimization was first carried out to obtain the relaxed atomic configurations before evaluating the electronic and optical responses of the doped systems. The calculated PBE band gap decreases from 0.82 eV for pure ZnO to 0.71, 0.55, and 0.38 eV, respectively, indicating a significant modification of the electronic structure after doping. Density of states (DOS) analysis indicates that Sn-derived electronic states emerge near the conduction-band region, leading to modifications of the band-edge structure and enhanced electronic transitions. Optical calculations further reveal increased low-energy absorption and a shift of the optical response toward the visible-light region after Sn incorporation, suggesting improved light-harvesting capability. Although the absolute band-gap values are underestimated compared with experiment, the observed trend provides meaningful insight into the role of Sn concentration in tuning ZnO properties. These results demonstrate that substitutional Sn doping is an effective strategy for tuning the electronic and optical properties of ZnO and improving its potential for visible-light optoelectronic and photovoltaic applications.